2012
DOI: 10.1089/apc.2012.0189
|View full text |Cite
|
Sign up to set email alerts
|

Impact of HIV-Specialized Pharmacies on Adherence and Persistence with Antiretroviral Therapy

Abstract: Patient adherence (the degree to which patients follow their therapeutic regimen as prescribed within a set period of time) and persistence (the time to treatment discontinuation, with a permissible gap) with drug therapy are essential components of HIV/AIDS treatment. Select community pharmacies offer specialized services for HIV/AIDS patients to help combat some of the barriers to adherence and persistence. We assessed adherence and persistence with antiretroviral therapy (ART) for patients using HIV-special… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
47
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(51 citation statements)
references
References 32 publications
2
47
1
Order By: Relevance
“…Lastly, a study by Barlow et al (2012) showed that, in addition to improvements in medication adherence, significant reduction in medical costs was documented for 3 years of participation in specialty pharmacy services versus retail pharmacy services for RA patients. 22,[34][35][36][37][38] Our findings suggest that specialty pharmacy programs can improve the management and medication adherence of patients with renal transplants and simultaneously reduce overall health care costs, which is similar to findings in previous studies. 1,17,22,[34][35][36][37][38] This study demonstrates the value of specialty pharmacy programs in improving adherence to oral transplant products in the first year post-implementation of the program.…”
Section: Limitationssupporting
confidence: 83%
See 1 more Smart Citation
“…Lastly, a study by Barlow et al (2012) showed that, in addition to improvements in medication adherence, significant reduction in medical costs was documented for 3 years of participation in specialty pharmacy services versus retail pharmacy services for RA patients. 22,[34][35][36][37][38] Our findings suggest that specialty pharmacy programs can improve the management and medication adherence of patients with renal transplants and simultaneously reduce overall health care costs, which is similar to findings in previous studies. 1,17,22,[34][35][36][37][38] This study demonstrates the value of specialty pharmacy programs in improving adherence to oral transplant products in the first year post-implementation of the program.…”
Section: Limitationssupporting
confidence: 83%
“…22,[34][35][36][37][38] Our findings suggest that specialty pharmacy programs can improve the management and medication adherence of patients with renal transplants and simultaneously reduce overall health care costs, which is similar to findings in previous studies. 1,17,22,[34][35][36][37][38] This study demonstrates the value of specialty pharmacy programs in improving adherence to oral transplant products in the first year post-implementation of the program. Substantial increases in several measures of adherence, including the number of oral transplant prescriptions filled and fewer gaps in therapy and discontinuation, were seen in patients who used the specialty pharmacy program in the first year.…”
Section: Limitationssupporting
confidence: 83%
“…24 The study demonstrated improvements in adherence as measured by proportion of days covered by antiretroviral drug prescriptions as well as persistence with remaining on antiretroviral therapy, though the absolute differences were modest.…”
Section: Supporting Literaturementioning
confidence: 83%
“…Five of these articles described community-based pharmacist-provided MTM. [21][22][23][24][25] Three community-based articles were related to the California HIV/AIDS specialty pharmacies selected to provide MTM services to HIV/AIDS Medi-Cal patients. 21 That study compared medical claims of HIV-infected patients in pilot pharmacies offering HIV MTM services with medical claims of HIVinfected patients in other Medi-Cal pharmacies that did not offer MTM services.…”
Section: Supporting Literaturementioning
confidence: 99%
“…It contributes to a greater adherence to treatment and an increase in quality of life. From this health-illness process perspective, many HIV carriers face an impact on their quality of life, which is understood as a person's perception of his position in life within the context of culture and system of values, in relation to his objectives, expectations, standards and preoccupations 3,4 . Quality of life related to health involves concepts associated with one's own health, functional status, psychological well-being, happiness and satisfaction of needs 1 .…”
Section: Introductionmentioning
confidence: 99%